Technology-enhanced professional development and internationalization: Transformative learning for English teachers in South Asia - Gyawali, Yadu Prasad; Mehndroo, Meghna (Journal of International Students, 2025)
This study examines how technology-enhanced professional development supports transformative teaching and learning among English teachers in higher education institutions in Nepal, India, and Bangladesh. Drawing on semi-structured interviews, the research explores teachers’ experiences with digital tools—including online learning platforms, interactive applications, and open educational resources—and how these technologies shape pedagogical practices. Findings reveal that technology integration improves instructional design, promotes innovative and student-centered approaches, and strengthens teacher confidence and classroom effectiveness. The study also identifies challenges, including limited digital literacy, inadequate infrastructure, and institutional barriers, that hinder sustained technology adoption. In addition, results highlight the potential of internationalization—through cross-border collaboration, shared digital resources, and global professional networks—to enrich English-language teaching across the region. Practical recommendations are offered for educators, departments, and institutions seeking to leverage technology to advance professional growth, enhance instructional quality, and promote transformative learning in higher education.